EKSPRESI SITOKIN TUMOR NECROSIS FACTOR (TNF-Î±) DAN INTERFERON (IFN-Î³) PADA SEL MDCK YANG DIINFEKSI VIRUS AVIAN INFLUENZA SUBTIPE H5N1 ASAL INDONESIA - Dharmayanti, NLP. Indi; Rillah, Ukhti Dwi; Syamsiah, Farida; Indriani, Risa (Perhimpunan Biologi Indonesia, 2014)
Patients with H5N1 disease have a characteristic complications of pneumonia with acute respiratory syndromedisterss and multi-organ failure associated with cytokine dysregulation, so it is suspected that the clinical forms ofsevere H5N1 disease in humans is caused by dysregulation of cytokine induction of H5N1 virus. Study oncytokines associated with H5N1 influenza virus infection is still limited, while animal studies using virus H5N1/97give conflicting results. Recent studies, showing that in fact the high cytokine is not a common form of the H5N1viruses, so Pathogenecity of H5N1 viruses were not only determined by whether or not the virus can inducehypercytokinemia. In this study we wanted to determine the phenotype of the Indonesia H5N1 virus in inducingcytokine expression. This study compared three Indonesian H5N1 viruses that have different genetic variations ofthe virus including the clade 2.1.1 and two other viruses included in clade 2.1.3 that were infected in Madin DarbyCanine Kidney (MDCK) cell. The MDCK cell that infected virus were observed for 72 hours. We observed theinfection during 72 hours and the cytokines expression were examined using RT-PCR method. The results showedthat the H5N1 influenza viruses used in this study showed the low expression of cytokines IFN-γ, and did notshow any expression of the TNF-α cytokines in MDCK cells infected with the H5N1 virus within 72 hours afterinfection.Keywords : Expression, H5N1 virus, Cytokines, sel Madin Darby Canine Kidney (MDCK)